AUDIT LAYANAN BERBASIS ITIL V4 DOMAIN SERVICE DESK, INCIDENT, DAN PROBLEM MANAGEMENT PADA PT XYZ - Ketut Tri Andika Ariana; Anak Agung Ngurah Hary Susila; Putu Veda Andreyana (Universitas Nusa Putra, 2025)
Information technology plays a crucial role in enhancing service quality and operational efficiency in the banking sector. PT XYZ has implemented the Melody service to facilitate online banking transactions for its customers. However, challenges remain, such as application performance issues and the effectiveness of customer complaint handling. This study conducted an IT service audit using the ITIL V4 framework, focusing on incident management, problem management, and service desk. The evaluation involves a maturity level analysis to identify gaps between the current state and user expectations. The results show that incident management is at level 3, problem management at level 1.5, and the service desk at level 1. This study provides phased recommendations for service improvement and develops an implementation plan to enhance IT service maturity sustainably at PT XYZ.